European Union law requirements related to the restitution of properties – does or under what conditions does the EU law require in practice the payment of a market-based compensation, and can that be enforced by EU law? of Properties - Korom, Ágoston; Szuchy, Róbert (The Opole Studies in Administration and Law, 2024)
The present paper addresses a specific issue, and analyses a concrete example in that regard, which issue arises almost exclusively in the former socialist countries: what requirements are determined by EU law in relation to the restitution of property expropriated in the concerned countries between 1945 and 1990? The principle of the free movement of capital particularly prohibits discrimination based on nationality. The general principles of EU law and the provisions of the Charter of Fundamental Rights of the European Union determine further requirements which Member States must take into account where the restitution measures they introduce implement EU law. In principle, EU law does not require that the compensation paid in the framework of restitution measures take the market value of the concerned real property into account. In its response given to the question of a written answer, the European Commission outlined also the manner in which the general principles and property rights should be considered where restitution measures are taken. The present paper covers also the analysis of whether the Romanian measure used as an example herein is compatible with the requirements prescribed by EU law, i.e. whether or not EU law requires the payment of market-based compensation in certain cases. This paper addresses also the access to and possible hindrances of the enforcement of the rights of the applicants deriving from EU law.